Simulation of low voltage dc-dc booster circuit with improved switch for amplification of biophotovoltaic cell output voltage - Alajmi, Shaea; Abdul Halin, Izhal; Mustapha, Faizal; Supeni, Eris Elianddy; Ibrahim, Irwan (Penerbit Akademia Baru, 2022)
Biophotovoltaic (BPV) cells otherwise called living solar cells are a clean energy-generating technology that uses photosynthetic organisms (cyanobacteria or microalgae) to produce electricity. However, the output voltage and current density of BPV cells are extremely low and the lifespan of BPV cells is short. In this article, a study based on computer simulation on the improvement of the switch of a low power DC to DC converter circuit is presented. A redesign of the circuit’s switch (NMOSFETs) shows that a 10.5 % increase in output voltage is achievable with an increase in efficiency of 3.4 %. Simulation shows that the increase in performance is due to the very low ON resistance of the newly designed switch.